2007
DOI: 10.1577/m05-157.1
|View full text |Cite
|
Sign up to set email alerts
|

Using Demographic Models to Determine Intrinsic Rate of Increase and Sustainable Fishing for Elasmobranchs: Pitfalls, Advances, and Applications

Abstract: Abstract.-Leslie matrices and life tables are demographic models commonly used to evaluate the ability of specific elasmobranch life history strategies to sustain given levels and patterns of fishing pressure. These models are generally density independent and provide an instantaneous rate of population growth for a specified set of life history traits that correspond to a specific population size. Many investigators are using these models to compute rates of population growth that they claim are estimates of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(74 citation statements)
references
References 22 publications
2
72
0
Order By: Relevance
“…For Prionace glauca, assuming that longevity is equal to13 years, t m =4.5 and GL =6.89, this author estimated a value of 0.328. For Dipturus laevis, using life tables, Gedamke et al (2007) estimated an r value of 0.45. Bousquet et al, (2008) estimated a value of r =0.4 for Georges bank haddock and 0.33 for albacore .…”
Section: Discussionmentioning
confidence: 99%
“…For Prionace glauca, assuming that longevity is equal to13 years, t m =4.5 and GL =6.89, this author estimated a value of 0.328. For Dipturus laevis, using life tables, Gedamke et al (2007) estimated an r value of 0.45. Bousquet et al, (2008) estimated a value of r =0.4 for Georges bank haddock and 0.33 for albacore .…”
Section: Discussionmentioning
confidence: 99%
“…The probability distribution for age-0 mortality was bounded by values that would create a population at equilibrium and a population showing slight increases in population, possibly due to compensatory increased survival in the age-0 cohort. It is likely that survivorship could increase to the level of the age-1 cohort as a compensatory mechanism to offset exploitation (Gedamke et al 2007). Various studies have found compensatory responses in elasmobranch populations following exploitation.…”
Section: Discussionmentioning
confidence: 99%
“…Although sustainable shark fisheries are theoretically possible, most industrial fisheries targeting elasmobranchs have been characterized by a "boom and bust" trajectory of landings, culminating in a major depletion of the exploited population (Castro et al 1999;Campana et al 2008). A few such fisheries that are apparently sustainable are now in place, but they have required more conservative benchmarks and perhaps a higher level of enforcement (Walker 1998;Gedamke et al 2007). All of these "success stories" have been managed nationally, not internationally.…”
Section: Fisheries Management By Rfmo: Kids In a Sandboxmentioning
confidence: 99%